1998
DOI: 10.2307/30141568
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Management of Patients and Employees Exposed to Pertussis

Abstract: Waning pertussis immunity and spread of pertussis by asymptomatic adults contributes to increased pertussis exposures of vulnerable children. The Santa Clara Valley Medical Center had 49 pertussis exposures between July 1, 1989, and June 30, 1997, which originated in pediatric units or clinics and had an impact on the Employee Health Service (EHS) and Emergency Department (ED). We have developed a standardized protocol for management of employees and patients exposed to pertussis. The protocol includes a check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Appropriate personnel were mobilized to deal with the outbreak, using previously developed procedures. 6 Beginning on May 30, 3,179 hospital employees received antibiotic prophylaxis over the next 4 weeks, after which the outbreak rapidly resolved. Because of the high frequency of intolerance to erythromycin, we elected to administer azithromycin (500 mg on day 1, followed by 250 mg on each of the next 4 days).…”
Section: Description Of the Outbreakmentioning
confidence: 99%
“…Appropriate personnel were mobilized to deal with the outbreak, using previously developed procedures. 6 Beginning on May 30, 3,179 hospital employees received antibiotic prophylaxis over the next 4 weeks, after which the outbreak rapidly resolved. Because of the high frequency of intolerance to erythromycin, we elected to administer azithromycin (500 mg on day 1, followed by 250 mg on each of the next 4 days).…”
Section: Description Of the Outbreakmentioning
confidence: 99%
“…Haiduven and colleagues reported that, between 1989 and 1997, their medical center had 49 pertussis exposures that originated in pediatric units or clinics. 22 Our experience is similar: 74 employees were exposed to 25 patients with pertussis between 1994 and 1998. 23 We found pertussis to be the third most common disease resulting in HCW exposure, following only varicellazoster and tuberculosis.…”
Section: Lessons F R O M N O S O C O M I a L Outbreaksmentioning
confidence: 64%
“…In this issue, Haiduven and colleagues report that their institution had 49 pertussis exposures over a 9-year period from 1989 to 1997. 18 Our experience is similar: 40 employees were exposed to 15 patients with pertussis from 1994 to 1997.…”
Section: Pertussis In Healthcare Facilitiesmentioning
confidence: 65%